The Association of Dietary Vitamin Intake Time Across a Day With Cardiovascular Disease and All-Cause Mortality - Gu, Wenbo; Wu, Huanyu; Hu, Cong; Xu, Jiaxu; Jiang, Hongyan; Long, Yujia; Han, Tianshu; Yang, Xue; Wei, Wei; Jiang, Wenbo (Frontiers in Cardiovascular Medicine, 2022)
Background Chrono-nutrition emphasized the importance of the intake time; however, less is known about the impact of dietary vitamin intake time on health. This study aimed to examine our hypothesis about which vitamin intake time could influence the natural course of cardiovascular disease (CVD). Methods A total of 27,455 adults enrolled in the National Health and Nutrition Examination Survey (NHANES) during 2003–2014 were recruited. The 12 dietary vitamin intakes in the morning, afternoon, and evening were categorized into tertiles or quartiles. Cox-proportional hazard regression models were developed to evaluate the association of vitamin intake time with CVD and all-cause mortalities. Results Compared with participants in the lowest quartile, participants in the highest quartile of dietary VB2 intake in the morning had significantly lowest mortality risk of CVD [hazard ratio (HR)VB2 = 0.75, 95% CI: 0.60–0.94, p = 0.017]; whereas, participants in the highest quartile of dietary-vitamin B6 (VB6), vitamin C (VC), vitamin E (VE), and folate-equivalent consumed in the evening showed the lowest risks of CVD (HRVB6 = 0.77, 95% CI: 0.60–0.99, p = 0.103; HRVC = 0.80, 95% CI: 0.65–0.98, p = 0.050; HRVE = 0.75, 95% CI: 0.56–0.99, p = 0.032; HRfolate–equivalent = 0.78, 95% CI: 0.63–0.97, p = 0.116) and all-cause mortalities (HRVB6 = 0.81, 95% CI: 0.71–0.93, p = 0.006; HRVC = 0.85, 95% CI: 0.76–0.95, p = 0.004; HRVE = 0.84, 95% CI: 0.72–0.97, p = 0.011; HRfolate–equivalent = 0.80, 95% CI: 0.71–0.90, p = 0.001). Moreover, equivalently replacing 10% intake of dietary VB6, VC, VE, and folate-equivalent in the morning with evening were associated with 4% (HRVB6 = 0.96, 95% CI: 0.92–0.99), 5% (HRVC = 0.95, 95% CI: 0.92–0.99), 4% (HRVE = 0.96, 95% CI: 0.91–0.99), and 5% (HRfolate–equivalent = 0.95, 95% CI: 0.92–0.99) lower risk of CVD mortality. Conclusion This study found that the optimal intake time of dietary VB2 was in the morning, and the optimal intake times of dietary VB6, VC, VE, and folate-equivalent were in the evening.